Protective Effects of Facilitated Removal of Blood Alcohol and Acetaldehyde Against Liver Injury in Animal Models Fed Alcohol and Anti‐HIV Drugs. (30th April 2019) - Han, Hui; He, Yuxin; Johnson, Heather; Mishra, Pratibha; Lee, Harrison; Ji, Cheng
Abstract : Background: We previously developed enzyme nanoparticles (ENP) of alcohol metabolism. This study was to evaluate protective effects of facilitated removal of blood alcohol and/or acetaldehyde on anti‐HIV drugs and alcohol‐induced liver injuries. Methods: ENP were prepared for degrading alcohol completely (ENP1) or partially into acetaldehyde (ENP2), which were applied to mice of acute binge or chronic‐binge alcohol feeding in the presence of antivirals (ritonavir and lopinavir). Liver pathologies were examined to assess the protective effects of ENP. Results: In the acute model, ENP1 and ENP2 reduced the blood alcohol concentration (BAC) by 41 and 32%, respectively, within 4 hr, whereas in control without ENP, BAC was reduced only by 15%. Blood acetaldehyde concentration (BADC) was increased by 39% in alcohol‐fed mice treated with ENP2 comparing to control. No significant effects of the anti‐HIV drugs on BAC or BADC were observed. Plasma alanine aminotransferase (ALT) and expression of liver TNF‐ α were both significantly increased in the alcohol‐fed mice, which were normalized by ENP1. In the presence of the antivirals, ALT was partially reduced by ENP1 or ENP2. In the chronic model, inflammation, fatty liver, and ALT were increased, which were deteriorated by the antivirals. ENP1 partially reduced BAC, BADC, ALT, and expression of inflammation markers of TNF‐ α, F4/80, and IL‐6 and lipogenic factors of ACC, LXR α, and SREBP1. ENP2 reduced BAC without significant effects on ALT, inflammation, or lipogenesis. Antivirals and alcohol synergistically increased expression of organelle stress markers of CHOP, sXBP‐1, ATF6, and GCP60. ENP1 reduced BAC, CHOP, and sXbp‐1. However, no effects of ENP1 were found on ATF6 or GCP60. Conclusions: Removal of blood alcohol and acetaldehyde by the ENP protects the liver against alcoholic injuries, and the protection is less effective in chronic alcohol and antiviral feeding due to additional drug‐induced organelle stresses. Abstract : Focal neutrophil infiltrations (A ). blood alcohol levels (B ), and alanine aminotransferase (C ), were not seen or reduced in AAC mice injected with ENPs. Naïve, without AAC or ENPs, E + PBS, with AAC and injection of phosphate‐buffered saline; E + ENP1, with AAC and ENPs for complete alcohol degradation; E + ENP2, with AAC and ENPs for partial alcohol degradation; E + PI + ENP1, with AAC, anti‐HIV protease inhibitors (PI), and ENP1; E + PI + ENP2, with AAC, PI, and ENP2; * p < 0.05, ** p < 0.01, *** p < 0.005 compared to Naïve.